War and diplomacy from world war 1 to the war on terrorism/ edited by Andrew Dorman and Greg Kennedy - Dorman , Andrew (ed.); Kennedy , Greg (ed.) (New Delhi, 2009)
Diplomatic efforts have shortened some of our worst wars and exacerbated others. The interaction of war and diplomacy is a theme avidly studied worldwide, considered by political and military strategists, and watched over by all those interested in international affairs. Written by renowned international scholars of diplomatic history, "War and Diplomacy" uses twentieth-and twenty-first-century case studies to review the evolution of this aspect of conflict prevention and reduction. Its contributors consider not only the changing philosophies of the participants, politicians, diplomats, and the military, but also the outside influences that may have changed the nature, and even the purpose, of peacekeeping and conflict resolution over the past century. As today a military threat can be applied without deploying vast armies and, conversely, can be reduced with pressure from international organizations rather than from an individual warlord, so the public's awareness of military conflict is now heightened by instantaneous broadcasts to worldwide audiences and by loud calls for diplomatic intervention. Regarding media and military affairs, therefore, evidence suggests the metaphoric pen can indeed be mightier than the sword. If you're interested in foreign affairs, modern history, and military strategy, "War and Diplomacy" will prove a valuable addition to your bookshelf.
Keywords: Diplomacy